Pengaruh Etanol dalam Minuman Beralkohol pada Kualitas Spermatozoa Tikus Putih. (Rattus Norvegicus) - Anis Satus Syarifah (2007)
Alcohol (ethanol-containing) drinks abuse may reduce testosterone level. The reduction of testosterone level may cause spermatogenesis reduction, affecting the quality and quantity of spermatozoa. The objective of this study was to identify whether ethanol in alcoholcontaining drinks could affect spermatozoa the motility and normal morphology ofspennatozoa in white rats (Rattus norvegicus). This was a laboratory experimental study using posttest only control group design. A number of 40 white rats were divided randomly into four groups, each comprised 10 rats. Control group was given with 3 ml distilled water twice a day using sonde. The groups of 15% ethanol, 30% ethanol, and 45% ethanol were given with ethanol per sonde in the dose of 0.72 grams, 1.44 grams, and 2.16 grams/200 grams white rats BW/day, respectively, which . were equal to 6 ml ethanol of 15%, 30% and 45%/200 grams white rats BW/day. The dose was given using sonde twice a day, each time a half of the dose. The treatment was given for 30 days at 6.30 a.m. and 5 p.m. Before the end of the study 2 white rats in 30% ethanol group and 4 white rats in 45% ethanol groups died. Results showed there was a reduction of spermatozoa motility and normal spermatozoa morphology, and there was significant diffe~nce in the mean of spermatozoa motility and normal spermatozoa morphology in control, 15% ethanol, 30% ethanol, and 45% ethanol groups (p < 0.05). Significant and negative correlation was found (p < 0.05) between ethanol dose and spermatozoa motility and normal spermatozoa morphology. In conclusion, alcohol drinks (containing ethanol) may cause the reduction of spermatozoa motility and normal spermatozoa morphology of white rats (Rattus norvegicus). The higher the ethanol concentration, the more the reduction of spermatozoa motility and normal spermatozoa morphology of white rats